Electronic and Steric Control of n→π* Interactions: Stabilization of the α‐Helix Conformation without a Hydrogen Bond. (7th March 2019) - Wenzell, Nicole A.; Ganguly, Himal K.; Pandey, Anil K.; Bhatt, Megh R.; Yap, Glenn P. A.; Zondlo, Neal J.
Abstract: The preferred conformations of peptides and proteins are dependent on local interactions that bias the conformational ensemble. The n→π* interaction between consecutive carbonyls promotes compact conformations, including the α‐helix and polyproline II helix. In order to further understand the n→π* interaction and to develop methods to promote defined conformational preferences through acyl N ‐capping motifs, a series of peptides was synthesized in which the electronic and steric properties of the acyl group were modified. Using NMR spectroscopy, van't Hoff analysis of enthalpies, X‐ray crystallography, and computational investigations, we observed that more electron‐rich donor carbonyls (pivaloyl, iso ‐butyryl, propionyl) promote stronger n→π* interactions and more compact conformations than acetyl or less electron‐rich donor carbonyls (methoxyacetyl, fluoroacetyl, formyl). X‐ray crystallography indicates a strong, electronically tunable preference for the α‐helix conformation, as observed directly on the φ and ψ torsion angles. Electron‐donating acyl groups promote the α‐helical conformation, even in the absence of the hydrogen bonding that stabilizes the α‐helix. In contrast, electron‐withdrawing acyl groups led to more extended conformations. More sterically demanding groups can promote trans amide bonds independent of the electronic effect on n→π* interactions. Chloroacetyl groups additionally promote n→π* interactions through the interaction of the chlorine lone pair with the proximal carbonyl π*. These data provide additional support for an important role of n→π* interactions in the conformational ensemble of disordered or unfolded proteins. Moreover, this work suggests that readily incorporated acyl N ‐capping motifs that modulate n→π* interactions may be employed rationally to promote conformational biases in peptides, with potential applications in molecular design and medicinal chemistry. Abstract : How is the α‐helix stabilized in the absence of hydrogen bonds? The strength of n→π* interactions was systematically modulated through the identity of the peptide acyl N ‐cap, with strong donors promoting α‐helix and polyproline II helix conformations, but weak donors resulting in more extended conformations. These results suggest the broader consideration of specific capping motifs for conformational control of peptides.